PENGARUH BACK MASSAGE DENGAN LAVENDER ESSENTIAL OIL PADA KUALITAS TIDUR IBU HAMIL TRIMESTER III - Aldifah Gyadi; Nella Vallen Ika Puspita; Mudy Oktiningrum (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2023)
Based on data from the Jepara District Health Office in 2021, the Tahunan area has the highest number of pregnancies, reaching 1204 pregnancies compared to other sub-districts in Jepara Regency, with 43.1% of them experiencing sleep disturbances. This study aims to determine the effect of back massage with lavender essential oil on the sleep quality of third-trimester pregnant women in the working area of the Annual Public Health Center, Jepara Regency. This type of research is a quasi-experimental one-group pretest-posttest design. The population taken in this study were 50 pregnant women in their third trimester in July – August 2022 in the working area of the Annual Health Center in Jepara Regency. The sampling technique was purposive, and a sample of 44 people was obtained. The data collection tool in this study used the Pittsburgh Sleep Quality Index (PSQI) questionnaire. Data analysis was performed using the Wilcoxon test. The results showed an effect of back massage with lavender essential oil on the sleep quality of third-trimester pregnant women in the working area of the Annual Public Health Center, Jepara Regency (p-value <0.05). The average PSQI score before a back massage with lavender essential oil was 8.95 and then decreased to 3.70 after giving a back massage with lavender essential oil. A decrease in PSQI scores indicates an improvement in sleep quality. Based on the Z value obtained, it was 5.811, which means that every one time back massage intervention with lavender essential oil given two times a week in the third trimester of pregnant women has the potential to improve sleep quality 5.811 times. Keywords: Back massage, Lavender essential oil, Sleep quality